Analysis of the Scientific Production of Environmental Consciousness and Sustainable Consciousness and Its Evolution in The Field of Education - José SILVA; Emilio MOYANO; Carlos GALLEGUILLOS; Rubén HURTADO; Ricardo JORQUERAand Karolina MUÑOZ (Communications of International Proceedings, 2025)
The sustainability crisis has caused a global concern about the problems and solutions linked to the environmental, social and economic environment, generating interest in understanding students' consciousness of such issues. The aim of this research is to show the scientific production of the evolution of environmental consciousness (EC) and sustainable consciousness (SC) within the field of education for sustainable development (SD). This was done through a systematic review between 2004 and 2025. The methodology was mixed with descriptive scope using the PRISMA method in the classification of articles using the Web of Sciences (WOS) and Scopus databases. The results showed the development of both concepts in international research organised by themes, the analysis of the methodological aspect and some of the most relevant findings. Themes such as EC and SC applied to students, curriculum and teacher competences, mostly quantitative, empirical and exploratory, were observed. It is suggested that both concepts have common aspects (knowingness, attitude and behavior) with an evolution in the dimensions, adding the environmental in EC, the social and the economic in SC. However, global complexity invites us to rethink other dimensions such as cultural, political or spiritual. This applies to any type of organization.
Keywords: Environmental consciousness; sustainability consciousness; education for sustainable development.